Pendampingan dan Pemanfaatan Marketplace Sebagai Digital Marketing Kerajinan Usaha Kreatif Aceh - Basri; Yuswardi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Online marketing, or what is known as marketplaces, has opened a new paradigm for marketing and launching products quickly and efficiently compared to the traditional method of selling through stores or point of sale. The key to online marketing success lies in the ability to first look at what and how your competitors operate and attract buyers with products and promotions that are different from other businesses his players. This is because the creative artisanal marketing strategies of various Aceh souvenirs, on average, are waiting for orders from merchants and buyers with traditional patterns. The purpose of this service activity is to advocate, advise and socialize the use of marketplaces in Aceh, especially in Sigli City, Pidie District, Aceh State, by creating a web marketplace for creative crafts sector. is to empower the craftsman and his MSMEs. The method of carrying out activities consists of three phases. Seminars, workshops, monitoring and evaluation. As a result of this activity, a web marketplace digi-expo.mwebs.id for online marketing through internet for creative craft industry in Aceh was implemented to increase the revenue from online sales of products.